The Works And Translatıons In The Kyrgyz Language In The Field Of Theology - GÖKÇE, Ferhat (Scientific Journal of Faculty of Theology, 2017)
In this article Introduced the works and translations in the field of theology. These Works and translations has been carried out by Osh State University of Theology Faculty since 2014. These works are supported by the Turkey Religious Foundation. These studies are aimed to prepare, printing and distribution of academic works in the field of theology, works and translations works according to the demands of peoples.